COLOURS: A SCIENTIFIC APPROACH - Bharadwaj, Venkatesh (International Journal of Research -GRANTHAALAYAH, 2014)
Colour is visual identification or perception of a property derived from spectrum of light by human eyes. When a beam of light from sun or light source passes through a glass prism, it dispersed in to seven colours of rainbow. Sunlight has a high color temperature, a fairly uniform spectrum and is considered a standard for white light. A rainbow is an optical and meteorological phenomenon caused by reflection and refraction of light in water droplets present in the atmosphere. The rainbow colours are violet, indigo, blue, green, yellow, orange and red (vibgyor). Electromagnetic radiation in the visible range is generally called as light.